Frequency of Left Atrial Enlargement According to Different Modes of Indexing in Overweight and Obese Individuals - Volkanovska Ilijevska, Cvetanka; Andova, Valentina; Georgievska Ismail, Ljubica (Macedonian Academy of Sciences and Arts, 2023)
Background: Current guidelines recommend indexing left atrial volume (LAV) by body surface area (BSA). However, in overweight and obese individuals this may result in the underestimation of left atrial enlargement (LAE). The aim of our study was to assess whether alternative LAV indexing to height and/or height-squared better identifies individuals with LAE among those who are overweight and/or obese. Methods: LAV was indexed to BSA (LAVI), height (LAVh), and height-squared (LAVh2) in 127 individuals with a mean age of 45.7 years and a mean body mass index (BMI) of 34.9 kg/m2 who underwent outpatient echocardiography at the University clinic of cardiology in Skopje. Results: LAVI, LAVh, and LAVh2 showed a progressive increase of respective values with the extent of BMI showing the most enlarged LA size in individuals with Class III obesity. There was a progressive significant increase in the prevalence of LAEh and LAEh2 in obese groups with the highest prevalence among those with class III obesity (p=0.002, p=0.002, respectively), on the contrary of LAEBSA where we could not find any significance in its distribution among obese classes. The greatest degree of reclassification occurred when indexing for height-squared, having relatively less reclassification when indexing for height (p=0.0001). The degree of reclassification varied depending on BMI with the greatest impact among the Class III obese patients, where as many as 76.5% and 88.2% of individuals were reclassified according to height or height-squared, respectively. Conclusions: The use of height, and especially height-squared, in comparison to BSA-based indexing methods are more successful in identifying the LAE prevalence in each class of obesity. Using allometric indexation leads to the significant reclassification of LA size from normal to dilated, especially in women and those with severe obesity, thereby providing an opportunity to identify more individuals at increased risk of adverse events.
Keywords: left atrial enlargement; alternative method of indexing; obesity